Froben Press Editions (1505–1559) in the Holdings of the Centre for Reformation and Renaissance Studies Library: A Brief Survey - Sebastiani, Valentina (Renaissance and Reformation / Renaissance et Réforme, 2014)
Analysis of the material aspects of books has opened new fields for historical enquiry that connect humanist learning, theology, and the press. The collaboration between Erasmus of Rotterdam and the printers Johannes and Hieronymus Froben of Basel between 1514 and 1536 offers itself as a vantage point from which to observe the making of written culture for humanists, allowing investigations into the media strategies and marketing communication tools employed to produce and disseminate humanist books in early modern Europe. This contribution provides a brief survey of Froben’s editions held in the collections of the Centre for Reformation and Renaissance Studies (CRRS) at Victoria University in the University of Toronto. A deep scrutiny of some of the CRRS library’s copies sheds light on the technical and economic aspects of Froben’s printing activity, while supplying significant information on Erasmus’s readership.